2000
DOI: 10.1029/2000gl011490
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for high velocity in Koyna seismic zone from P‐wave teleseismic imaging

Abstract: Abstract. Three-dimensional P-wave velocity structure of the crust and upper most mantle beneath the Koyna Seismic Zone (KSZ) was determined by inverting 780 P-wave teleseismic travel times recorded by a 20 station digital network. The velocity image obtained through damped least square was tested for its resolution using checkerboard approach. The results of the inversion show strong lateral velocity variations of 6% to 7% within the study region. A high velocity anomaly (2% to 5%) in the upper and lower crus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 20 publications
2
4
0
Order By: Relevance
“…2-4). This finding is strengthened by seismic tomographic results (high velocity anomaly of 2-5% coinciding with isostatically corrected +10 mGal gravity anomaly) beneath Koyna region (Sringesh et al, 2000) as well as drilling results from Mumbai offshore (Rathore et al, 2000). Comparative velocity distributions suggest that the underlying crust below Latur region may be more denser/mafic and thinner than Koyna.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…2-4). This finding is strengthened by seismic tomographic results (high velocity anomaly of 2-5% coinciding with isostatically corrected +10 mGal gravity anomaly) beneath Koyna region (Sringesh et al, 2000) as well as drilling results from Mumbai offshore (Rathore et al, 2000). Comparative velocity distributions suggest that the underlying crust below Latur region may be more denser/mafic and thinner than Koyna.…”
Section: Discussionsupporting
confidence: 51%
“…3), which indicates an even higher P velocity of 6.4 km/s at a depth of around one kilometer only. Presence of higher velocities below this region are supported by seismic tomographic studies (Sringesh et al, 2000) too, which indicate 2-5% high velocity anomaly in the crust below Koyna seismic zone, compared to much lower velocities (À2% to À5%) on its either side. For our study, we utilize the latest result of Krishna (2006).…”
Section: Latur and Koyna Seismic Zonesmentioning
confidence: 81%
“…Presence of higher velocity below this region are supported by seismic tomographic studies of Srinagesh et al (2000), who indicated 2% to 5% higher velocity anomaly in the crust below Koyna seismic zone compared to much lower velocities (-2% to -5%) on its either side.…”
Section: Koyna Seismic Zonementioning
confidence: 86%
“…Alternatively, stresses can also be caused due to large scale intrusive activity at crust/ mantle level, like that found below Koyna and several regions of central India. In case of Koyna, seismic tomographic studies indicate presence of 2 to 5% high velocity anomaly in the crust apparently related to an intrusive body (Srinagesh et al 2000).…”
Section: South Indian Shield Global Shield and Platform Ak 135mentioning
confidence: 99%
“…As discussed, TB1 appears to passes through the Koyna-Warna seismic zone. The near surface and complex high velocity, noted by Srinagesh et al (2000) under the Koyna region, could be caused by the schist (or greenstone) belts associated with the accretionary corridor TB1. Ramakrishnan et al (1976) and Radhakrishna (1989) have also suggested the presence of two terranes across the Chitradurga and Closepet corridor.…”
Section: Deep Seismic Studiesmentioning
confidence: 99%